Prospective associations between nicotine beliefs and tobacco-related susceptibility, curiosity, and use in U.S. adults - Villanti, Andrea C. (Prev Med, 2020)
Low harm perceptions of tobacco products have been associated with use of those products in youth and adults, but this relationship has not been assessed for nicotine beliefs. This study used data from a national sample of adults aged 18–40 in Wave 9 (Spring 2016) of the Truth Initiative Young Adult Cohort Study to examine correlations and prospective associations between the latent classes of nicotine beliefs and susceptibility, curiosity, and use of tobacco products in 3,122 adults who also completed Wave 10 (Fall 2016). At Wave 9, four latent classes of beliefs characterized the role of nicotine in the health risks of smoking: Class 1, large role, 51%; Class 2, large role/don’t know, 9.4%; Class 3, small role in health, 32.5%; and Class 4, none/small role in cancer, 7.5%. Latent classes of nicotine beliefs were highly correlated with susceptibility and curiosity to use cigarettes, e-cigarettes, and hookah, as well as past 30-day use of a range of tobacco products at Wave 9 among never users. Classes 3 and 4 had the highest prevalence of past 30-day tobacco use; never users in these classes reported the greatest susceptibility to try cigarettes, hookah, and e-cigarettes at Wave 9. Class 4 had higher odds of increased e-cigarettes use at follow-up compared to Class 1. There were few prospective associations between nicotine beliefs latent class, susceptibility, and curiosity at Wave 10. Nicotine beliefs are associated with tobacco-related outcomes and, if assessed, may provide novel information to guide tobacco prevention and intervention efforts.